2018
DOI: 10.1017/rdc.2018.11
|View full text |Cite
|
Sign up to set email alerts
|

The New Gas Ion Source at CEDAD: Improved Performances and First 14C Environmental Applications

Abstract: A new sputtering ion source has been installed at CEDAD (Centre for Dating and Diagnostics) at the University of Salento in Lecce, Italy. The installation of the new ion source, capable of accepting both solid and gas samples, required significant modifications of the existing low energy injector of the accelerator mass spectrometry (AMS) system. The new ion source is connected, through an in-house designed gas handling interface, to an elemental analyzer which combusts the samples to carbon dioxide and splits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Although this dedicated microsample procedure is effective in ensuring the reliability of a result, its implementation requires the preparation, graphitization and analysis of a large amount of primary standards, blanks and secondary standards for a single unknown sample. A gas source will be installed on the AMS ARTEMIS for the measurement of smaller samples (Bronk Ramsey et al 2004;Xu et al 2007;Wacker et al 2013;Calcagnile et al 2018). It has the advantage of removing the graphitization step from the preparation procedure and reducing the risks of contaminating the sample during this processing step.…”
Section: Resultsmentioning
confidence: 99%
“…Although this dedicated microsample procedure is effective in ensuring the reliability of a result, its implementation requires the preparation, graphitization and analysis of a large amount of primary standards, blanks and secondary standards for a single unknown sample. A gas source will be installed on the AMS ARTEMIS for the measurement of smaller samples (Bronk Ramsey et al 2004;Xu et al 2007;Wacker et al 2013;Calcagnile et al 2018). It has the advantage of removing the graphitization step from the preparation procedure and reducing the risks of contaminating the sample during this processing step.…”
Section: Resultsmentioning
confidence: 99%
“…From the experimental point of view the determination of the biogenic content in the carbonaceous fraction of PM can be performed by AMS (Accelerator Mass Spectrometry) which allows the determination of the 14 C/ 12 C isotopic ratio with a sensitivity in the 10 −16 range and precision levels of the order of 0.2-0.3% [5][6][7]. The major issue is indeed related to the amount of material needed for the analyses.…”
Section: Jinst 15 C05025 2 Materials and Methodsmentioning
confidence: 99%
“…We present a new experimental set-up developed at CEDAD-Centre for Applied Physics, Dating and Diagnostics allowing the determination of the 14 C content by AMS (Accelerator Mass Spectrometry) on PM samples with masses in the microgram range. The set-up is based on an automatic combustion system coupled, through a gas handling interface, to a hybrid ion source designed to accept samples both in the solid and gaseous form and allowing the determination of the 14 C/ 12 C ratio by AMS on samples with masses down to 10-20 µg of carbon with precision of the order of 0.5-1% [5,6]. We present the performances of the set-up for the analysis of carbonaceous fraction of PM10 and PM2.5 sampled on quartz filters and discuss them in terms of instrumental sensitivity, precision and accuracy.…”
mentioning
confidence: 99%
“…The experimental set-up, described in detail by Quarta et al (2020), is based on an automatic combustion system coupled, through a gas-handling interface, to a hybrid ion source designed to accept samples both in solid and in gaseous form. Overall efficiencies of the order of 4% were shown such as the capability to measure both 13 C/ 12 C and 14 C/ 12 C ratios by AMS with uncertainty levels of 0.5-1% (Calcagnile et al, 2018). Tests performed on field blanks showed that the contribution of carbon fractions was too low and the effect on the calculated value was negligible.…”
Section: Ams Technique and 14 C Analysis Of Total Carbonmentioning
confidence: 99%